Investigating chemical, antioxidant, and sensory properties of chocolate fortified with cactus stems powder - Angor, Malak; Al Khalaileh, Nazieh; Al-Marazeeq, Khaled; Al-Rousan, Walid; Ajo, Radwan (Frontiers in Sustainable Food Systems, 2023)
Objective The present study aimed to examine the sensory, antioxidant, and chemical characteristics of chocolate that were enhanced with a powder derived from cactus leaves. Methods Treatments were prepared by fortified chocolate with cactus stems powder at different levels (0%, 3%, 5%, and 7%) w/w. Results The results indicated that fortification of chocolate with cactus stems powder increased significantly (p ≤ 0.05) moisture, protein, ash, total carbohydrate, and fiber of chocolate treatments with cactus stems powder, in comparison to the control group (0%). On the contrary, there was a notable (p ≤ 0.05) reduction in fat content in all the treatments that contained cactus leaf powder. Conclusions The augmentation of cactus stems powder in chocolate treatments had a positive impact on their antioxidant activity, which increased with increasing the concentration of the powder. In addition, this inclusion of cactus stems powder aided in lowering the oxidative degradation of the chocolate treatments. The sensory analysis findings revealed no significant difference between mean ratings for the overall acceptability of control chocolate and fortified chocolate treatments (p ≤ 0.05).